Kaji Numerik Pengaruh Beban Awal, Kecepatan Permukaan Dan Radius Bearing Terhadap Ketebalan Lapisan Film Dan Tekanan Elastohydrodynamic Pada Cylindrical Roller Bearing Menggunakan Metode Beda Hingga - Zulfikar, Zeta; Cupu, Dedi Rosa Putra; Nazaruddin, Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Contact between the roller element with the inner or outer ring produces enormous pressure which can cause friction between the surfaces of the two objects. The continuous friction will result in wear and using lubricant between the two contacting surfaces becomes an important role to reduce friction as well as wear. There are several types of lubrication, one of them is elastohydrodinamic lubrication. In this study the numerical method of Finite Difference Method is used to solve Reynolds equation in order to investigate the effect of basic parameters such as initial load, surface speed and radius of the cylindrical roller bearing. A single contact of cylinder roller and inner ring is modeled as a contact between a solid cylinder and flat plate. The influence of temperature, non-newtonian fluids and dynamic loads are ignored in this research. Central-difference scheme in the Finite Element Method is used to solve the Reynolds equation for calculating the elastohydrodynamic pressure that occurs on a contact. The results obtained show that there is an influence of the initial load, velocity and also the radius of the pressure generated at the time of contact between the solid cylindrical bearing element and the thickness of the film layer formed between the two surfaces of the object. The greater load given will increase the maximum pressure, but reduce the minimum film thickness. While when given variations in velocity, increasing the minimum value of film thickness and reduce the maximum pressure. Likewise what happens when variations in radius are given, increasing the minimum value of film thickness and reducing the value of maximum pressure. Keywords: Elastohydrodynamic Lubrication, Film Thickness, Elastohydrodynamic Pressure, Finite Element Method